MODEL PENGEMBANGAN PARSISIPASI KELUARGA PASIEN DENGAN PREVENTIONT OF DISABILITY DI RS SUMBERGLAGAH MOJOKERTO - Wahyuni, Lutfi Wahyuni; Wahyuningsih, Binarti Dwi; Yuniarti, Enny Virda (Unusa Press, 2018)
The onset of disability prevention efforts on lepers who have yet to experience a disability. One of the factors that influence self-care lepers is family participation. The purpose of this research was to prove the relationship family participation with in the prevention of disability lepers. This Design of this research was Analytic korelasionalwith crossectional approach. Population research namely whole leprosy in the outpatient room  atSumberglagah  hospital Pacet Mojokerto as much as 137 survivors. Samples taken with the concecutivesamplingtechnique as much as 20  respondents. There are two research variablewere family participation as the independent variable and the dependent variable as a disability prevention. Data collected by questionnaire instrument. Then the results of and tested with Chi-Square. The results showed that respondents from 11 his family participate in the prevention of disability most respondents can prevent the onset of disability as many as 10 respondents (55%) and 9 (45%) respondents were not able to prevent the occurrence of disability. and 19 respondents whose families participate less mostly not able to prevent the occurrence of defects as much as 11 respondents (55%) and which can prevent the onset of disability 9 respondents (45%). Chi-Square test results retrieved data ρ = 0.008  <α = 0.05 it means H1 accepted so there is a connection With Family participation in the prevention of disability. This shows the more active participation of the family given in lepers will be leprosy will be able to do the prevention of leprosy disability well anyway. So expect more families be active in the care of lepers in the home and can encourage the sufferer to be able to do self care on a regular basis in preventing the onset of disability